The Reactants’ Phase State: A Nonnegligible Factor in Tetralin Hydrogenation Catalysts Evaluation - Mingjian Luo; Qingfa Wang; Xiangwen Zhang; Bing Hu (International Journal of Chemical Engineering)
The effects of reactants’ phase states (gas-liquid and single gas phase) on tetralin hydrogenation were investigated in the fixed bed. The kinetics of tetralin hydrogenation under different phase states was analyzed. Results showed that, without phase transition, the tetralin conversion increased with the rise of temperature. However, it decreased dramatically around the dew point of the feed at which the reactants’ phase state transferred from gas-liquid phase into gas phase. It was also observed that the gas-liquid phase state was favorable to reduce the deactivation of catalyst in the tetralin hydrogenation.